2013
DOI: 10.1159/000357024
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Arthropod Sex Determination by Endosymbionts: Diversity and Molecular Mechanisms

Abstract: Arthropods exhibit a large variety of sex determination systems both at the chromosomal and molecular level. Male heterogamety, female heterogamety, and haplodiploidy occur frequently, but partially different genes are involved. Endosymbionts, such as Wolbachia, Cardinium,Rickettsia, and Spiroplasma, can manipulate host reproduction and sex determination. Four major reproductive manipulation types are distinguished: cytoplasmic incompatibility, thelytokous parthenogenesis, male killing, and feminization. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
57
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 127 publications
(169 reference statements)
0
57
0
1
Order By: Relevance
“…Heritable bacterial endosymbionts are widespread in arthropods. They utilize diverse strategies to spread within host populations, such as provision of essential nutrients (Gündüz & Douglas, ; Hosokawa, Koga, Kikuchi, Meng, & Fukatsu, ), defense against parasites (Hedges, Brownlie, O'Neill, & Johnson, ; Vorburger, Gehrer, & Rodriguez, ), and reproductive manipulation (Ma, Vavre, & Beukeboom, ).…”
Section: Introductionmentioning
confidence: 99%
“…Heritable bacterial endosymbionts are widespread in arthropods. They utilize diverse strategies to spread within host populations, such as provision of essential nutrients (Gündüz & Douglas, ; Hosokawa, Koga, Kikuchi, Meng, & Fukatsu, ), defense against parasites (Hedges, Brownlie, O'Neill, & Johnson, ; Vorburger, Gehrer, & Rodriguez, ), and reproductive manipulation (Ma, Vavre, & Beukeboom, ).…”
Section: Introductionmentioning
confidence: 99%
“…An exception to this constraint applies to those species in which asexuality is induced by infection with bacterial endosymbionts, such as A. japonica (Kremer et al , 2009; Reumer et al , 2012). Endosymbiont-induced asexuality is mainly found among wasps and among other groups in which sexual species are characterized by haplodiploid sex determination (Werren, 1997; Werren et al , 2008; Mateo Leach et al , 2009; Giorgini et al , 2010; Kageyama et al , 2012; Ma et al , 2014), although it has also been suggested to occur in species with other sex determination systems (for example, Pike and Kingcombe, 2009). Under haplodiploidy, females develop from fertilized, diploid eggs, whereas males develop from unfertilized, haploid eggs (Whiting, 1933).…”
Section: Introductionmentioning
confidence: 99%
“…CI is the most frequent host manipulation by Wolbachia and has thus far been reported for six insect orders (Coleoptera, Diptera, Hemiptera, Hymenoptera, Lepidoptera, and Orthoptera) and terrestrial crustaceans and mites (Ma et al 2013), while Cardinium-mediated CI has only been reported for two parasitoid wasp species (Hymenoptera), one planthopper species (Hemiptera) and a number of mite species (Hunter et al 2003;Breeuwer et al 2012;Nakamura et al 2012;Gebiola et al 2016a, b). Bacterially mediated CI is a postzygotic effect that occurs when infected males mate with uninfected females, or with females infected with bacteria that cannot rescue CI.…”
mentioning
confidence: 99%